Two-center approach to fully differential positron-impact ionization of hydrogen - Kadyrov, Alisher; Bailey, Jackson; Bray, Igor; Stelbovics, Andris (American Physical Society, 2014)
The two-center approach to positron-impact ionization of atomic hydrogen is shown to follow from the exact post form of the breakup amplitude [Kadyrov, Bray, Mukhamedzhanov and Stelbovics Phys. Rev. Lett. 101 230405 (2008)]. In such approaches distinct ionization amplitudes arise from each center for the same ionization process. The fully differential cross section for the positron-impact breakup of atomic hydrogen is calculated including direct ionization of the target and electron capture into the positronium continuum. We show that the coherent combination of the amplitudes leads to oscillations in the differential cross sections, whereas the incoherent combination does not. The latter has also the advantage of being consistent with the unitary close-coupling formalism.